2019
DOI: 10.26575/daj.v32i2.285
|View full text |Cite
|
Sign up to set email alerts
|

A sub-continent of caries

Abstract: The most recognizable pathological condition of the human oral cavity is, arguably, dental caries. Beyond a direct impact on oral health, caries presence (or absence) provides important data for bioarchaeologists—to help reconstruct the diet of past populations and individuals. This study explores such data in 44 samples (n=1,963 individuals, 62,816 teeth) dating between 10,000 BP and recent times across the African sub-continent. It is, to date, the most extensive investigation of its kind in this part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A recent study of caries in the African sub-continent through time found that hunter-gatherer groups had a caries prevalence similar to that of the South African fossil hominins analysed here. 59 This includes groups relevant to the present study because of geographic proximity, i.e. prehistoric and historic Khoesan peoples.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of caries in the African sub-continent through time found that hunter-gatherer groups had a caries prevalence similar to that of the South African fossil hominins analysed here. 59 This includes groups relevant to the present study because of geographic proximity, i.e. prehistoric and historic Khoesan peoples.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the same approach might also help to elucidate the evolutionary history of both commensal and pathogenic taxa within the human oral microbiome. Periodontitis and dental caries have likely afflicted humans since their origins [14][15][16][17]. They may now be amenable to population genetic analyses because a landmark publication by Adler et al in 2013 [18] demonstrated that dental calculus (calcified dental plaque) from the teeth of skeletons that were up to 7500 years old could contain relatively well preserved ancient bacterial DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Given the above synergistic relationship, palaeodietary studies often macroscopically examine dental diseases and dental wear in tandem to explore past population socioeconomic dynamics and cultural interactions (Avery et al, 2019;Karapetian et al, 2021;Keenleyside, 2008;Zhang et al, 2016). There are studies, however, occasionally focusing on single dental diseases, mostly caries (e.g., Bertilsson et al, 2021;Burns, 1979;Carter and Irish, 2019;Da-Gloria et al, 2017;Liebe-Harkort, 2012;Mant and Roberts, 2015;Nagaoka and Abe, 2018;Whittaker et al, 1981). In addition, the last two decades have seen a growing trend towards combining dental disease macroscopic data with dietary stable isotope analysis (e.g., Beck et al, 2018;Bondioli et al, 2016;Fabra and González, 2019;Jílková et al, 2019;Lillie and Richards, 2000;Prowse, 2011;Prowse et al, 2008;Toso et al, 2019).…”
Section: The Synergistic Relationship Between Dental Diseases and Den...mentioning
confidence: 99%